Spondias purpurea L. (Anacardiaceae) fruits flours at different maturation stages: Drying kinetics, mathematical modelling, characterization and correlation analysis - Álvaro Gustavo Ferreira da Silva; Franciscleudo Bezerra da Costa; Ana Marinho do Nascimento; Giuliana Naiara Barros Sales; Jéssica Leite da Silva; Alzira Maria de Sousa Silva Neta; Wellington Souto Ribeiro; Toshik Iarley da Silva; Bruno Fonsêca Feitosa (Heliyon)
The aim of this study was to examine the drying kinetics of Spondias purpurea L. fruits at various maturation stages (I to V) using a range of mathematical models (Henderson and Pabis, Lewis, Logarithmic, Midilli, and Page). Additionally, an assessment of the resulting flours' quality was conducted. The stabilization phase of S. purpurea fruit drying kinetics commenced at 420 min for maturation stages I and III, and at 480 min for the remaining stages. All employed mathematical models effectively characterized the drying process, exhibiting R2 values exceeding 0.99, MSD below 0.03, and X2 below 0.0009. Flours demonstrated increased color intensity with higher levels of flavonoids and anthocyanins, showing a positive correlation. Immature fruits yielded flours with elevated titratable acidity, total chlorophylls, phenolic compounds, and density. In contrast, fruits in the final maturation stages produced flours with higher yield, levels of reducing sugars, total carotenoids, flavonoids, and anthocyanins. The results indicate that flours derived from ripe fruits exhibited higher yield, moisture content, pH, soluble solids, and reducing sugars, while titratable acidity was higher in green fruits. Bioactive compounds such as total chlorophyll, ascorbic acid, and phenolic compounds decreased with ripening, whereas total carotenoids increased due to chlorophyll degradation and carotenoid biosynthesis. Anthocyanin and total flavonoid levels increased in the final stages of ripening. Thus, the developmental stage directly influences the physicochemical and functional characteristics of S. purpurea fruit flours. This comprehensive analysis offers valuable insights into the drying kinetics of S. purpurea fruits and underscores the influence of maturation stages on the quality attributes of the resultant flours.